Program Kemitraan Masyarakat (PKM) Guru SMA di Kota dan Kabupaten Bandung dalam Kegiatan Pengolahan Data Berbasis E-Learning - Jusep Saputra; Thesa Kandaga; Anggoro Ari Nurcahyo (Universitas Mathla'ul Anwar Banten, 2018)
COMMUNITY PARTNERSHIP PROGRAM (CPP/PKM) HIGH SCHOOL TEACHERS IN CITY AND BANDUNG REGENCY IN E-LEARNING DATA PROCESSING ACTIVITIES. The purpose of the Subject Teachers Consultation (STC) is that they are able to support teacher competencies. The STC included in the Community Partnership Program (CPP) is the Bandung and City Mathematics STC. Problems with both partners are: (1) Understanding of some teachers in collecting data according to the formulation of research problems is still lacking, (2) Teachers do not know e-learning applications that use video conferencing. (3) Some teachers in processing research data with SPSS are still lacking, (4) some teachers have not been skilled in making scientific articles. The two partners' solution-resolution procedures will be carried out by the team are training, guidance, and accompaniment. CPP was attended by 14 Mathematics Teachers from the City of Bandung, and 17 Mathematics Teachers The first meeting resulted in the following conclusions: (1) The quality of CPP in formulating problems, testing instruments, using SPSS features, and video conferencing was conducted very good, (2) The abilities of teachers to understand, master, and train in making either test or non-test research instruments are in a pretty good category, (3) t The teacher's ability to input data according to data or the scale of the data is in a good category, (4) The teacher's ability to use video conferencing and guidance in doing the work is in good category, 5) The ability to teach research data with SPSS; analyze, and interpret research data in the good category, (6) The scientific ability is in a good enough category.